2012
DOI: 10.1080/10538720.2012.643217
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Loneliness in Midlife and Older Gay and Bisexual Men

Abstract: This study examined the correlates of psychosocial and behavioral factors on loneliness in midlife and older gay and bisexual men in South Florida. A community-based sample of 802 self-identified gay and bisexual men ages 40 to 94 years completed standardized measures of life orientation (optimism versus pessimism), internalized homonegativity, coping self-efficacy, and loneliness. Multivariate modeling successfully explained 45% of the variance in loneliness, which was significantly related to life orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 66 publications
0
26
2
3
Order By: Relevance
“…In an ethnographic study of Dutch gay men (Aggarwal & Gerrets, 2014), a common reported theme was diminished self-esteem and degraded self-worth that led to chronic feelings of increased vulnerability to social rejection. These maladaptive cognitive biases can lead to increased levels of internalized disapproval of one's own sexual orientation (Jacobs & Kane, 2012) and negative interactions with others (Coyne, 1976) that may perpetuate depressive symptoms and feelings of loneliness.…”
Section: Minority Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ethnographic study of Dutch gay men (Aggarwal & Gerrets, 2014), a common reported theme was diminished self-esteem and degraded self-worth that led to chronic feelings of increased vulnerability to social rejection. These maladaptive cognitive biases can lead to increased levels of internalized disapproval of one's own sexual orientation (Jacobs & Kane, 2012) and negative interactions with others (Coyne, 1976) that may perpetuate depressive symptoms and feelings of loneliness.…”
Section: Minority Groupsmentioning
confidence: 99%
“…Rates of loneliness, similarly, are higher in Dutch sexual minority groups than in heterosexual groups (Fokkema & Kuyper, 2009). Rates of loneliness in U.S. sexual minority populations are less clear, as studies on loneliness in have not included heterosexual samples (Jacobs & Kane, 2012;Kim & Fredriksen-Goldsen, 2016).…”
mentioning
confidence: 99%
“…Loneliness is also associated with having lower socio-economic status (3,7,9,11). Finally, higher levels of social self-efficacy (feelings of being in control in social situations) (30), and coping selfefficacy (31) are associated with less loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…D'autre part, le sentiment de solitude peut affecter la santé mentale des aînés gais et lesbiennes et il semble que le degré d'homophobie intériorisée peut intensifier ce sentiment (Jacobs et Kane, 2012). La faible intensité de la vie sociale et la solitude ressentie font partie des difficultés fréquemment rapportées par les aînés GLB .…”
Section: Les Facteurs Affectant Négativement La Santé Mentaleunclassified
“…Jacobs et Kane (2012) proposent plusieurs recommandations pour améliorer la formation des intervenants auprès des hommes gais et bisexuels aînés. Selon eux, une meilleure connaissance du contexte sociohistorique dans lequel ceux-ci ont vécu et des impacts de l'homophobie intériorisée, en particulier chez les hommes vieillissants, leur permettrait de concevoir des stratégies visant à changer leurs perceptions et leurs attitudes négatives vis-à-vis de leur orientation sexuelle.…”
Section: Implications Et Recommandationsunclassified